The Growth of the Automobile Industry : Toyota’s Dominance in United States - Uchil, Samarth Anil; Yazdanifard, Rashad (Journal of Research in Marketing (ISSN: 2292-9355), 2014)
During the last decade, the advancement in production and management systems has revolutionized the automobile industry. The industry has witnessed the opening up and growth of several emerging markets. The automotive industry is now facing new and pressing challenges. Globalization, digitalization and increasing competition in the market are changing the face of the industry. Size of the organization is no longer a guarantee of success. Only those companies that find new innovative techniques to create value can prosper in the future. The purpose of this paper is to present a short overview of the automotive industry today and highlight challenges that are faced the industry. We are also going to overview Toyota’s dominance in the US market, strategies used by them and how they were able to overcome the challenges and competition they faced in a foreign market, and how upcoming automobile companies can use Toyota’s strategies to grow in the current market.